HUBUNGAN MODEL PEMBELAJARAN FLIPPED CLASSROOM DENGAN KEAKTIFAN BELAJAR SISWA MATERI SISTEM PENCERNAAN DI KELAS V SD - Anas Tasya; Destrinelli; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the relationship between the Flipped Classroom learning model and student learning engagement in the digestive system topic among fifth- grade students at UPT SDN 11 Padang Ganting. Using a quantitative approach, this correlational study analyzes the relationship between two variables. The sampling technique employed was total sampling, involving all 21 fifth-grade studentsl. Validity and reliability tests confirmed that all items were valid and reliable. The Pearson product-moment correlation test showed a p-value (Sig. 2-tailed) of 0.020, which is less than 0.05. This indicates sufficient statistical evidence to support the existence of a relationship between the flipped classroom model and student engagement. The correlation coefficient was 0.502, indicating a moderately strong positive relationship. This suggests that the more effectively the Flipped Classroom model is implemented, the higher the level of student engagement. In conclusion, the study found a moderately strong relationship between the Flipped Classroom learning model and student engagement in learning about the digestive system among fifth-grade students at UPT SDN 11 Padang Ganting.